Effect of Some Manfacturing Parameters on Machining of Extruded Al-Al2O3 Composites. (17th April 2012) - Fathy, A.; Abdelhameed, M.; Shehata, F.
Abstract : A wide range of particulate metal matrix composites (PMMCs) of alumina and aluminum powders was formed using powder metallurgy techniques followed by extrusions at various extrusion ratios. The machining characteristics of the extruded PMMC were investigated. Results showed significant effects of weight fractions of reinforcement and extrusion ratios on tool wear and surface integrity of machined surface. The wear rate of cutting tool decreased rapidly with increasing the cutting parameters: cutting speed, feed, and depth of cut, however cutting speed is shown to be more effective. Sudden breakage of tool inserts occurred when the experiment started at high cutting speed. Wear rate has also decreased by decreasing volume fraction of reinforcement particles. Coating carbide tools have significantly improved the tool life. Coated tools showed 5% decrease in flank wear size compared to uncoated tools. This was valid within tested range of weight fractions and extrusion ratios. The surface finish of machined surfaces deteriorated when coated carbide tools were used. However, surface finish did not change significantly when volume fractions or extrusion ratios were altered.